2022
DOI: 10.1097/mlr.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Different Self-reported Social Risks and Neighborhood-level Resources in Medicaid Patients

Abstract: Background: Adverse social conditions are a key contributor to health disparities. Improved understanding of how social risk factors interact with each other and with neighborhood characteristics may inform efforts to reduce health disparities.Data: A questionnaire of 29,281 patients was collected through the enrollment of Medicaid beneficiaries in a large Northern California integrated health care delivery system between May 2016 and February 2020.Exposures: Living in the least resourced quartile of neighborh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…This suggests that incorporating community-level social risk factors, even at the granular census block group level, may not meaningfully improve the calibration of risk adjustment models among Medicare beneficiaries. Whereas we believe our study is the first to evaluate this association in a Medicare Advantage population and using the ADI, prior research has found measures of community-level social risk to be poor proxies for individual social needs …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests that incorporating community-level social risk factors, even at the granular census block group level, may not meaningfully improve the calibration of risk adjustment models among Medicare beneficiaries. Whereas we believe our study is the first to evaluate this association in a Medicare Advantage population and using the ADI, prior research has found measures of community-level social risk to be poor proxies for individual social needs …”
Section: Discussionmentioning
confidence: 87%
“…Whereas we believe our study is the first to evaluate this association in a Medicare Advantage population and using the ADI, prior research has found measures of community-level social risk to be poor proxies for individual social needs. 22,23 Although relatively weak in magnitude, there was a significant association between ADI and health care spending. Considered alone, increases in ADI (ie, more disadvantage) were associated with increased spending.…”
Section: Discussionmentioning
confidence: 95%
“…9 Seven articles (39%) were published between 2013 and 2015, [8][9][10][11][12]16,20 while the remaining articles (61%) were published between 2016 and 2018. 4,[13][14][15][17][18][19][21][22][23][24][25][26][27][28][29][30][31]33 Sixteen articles (89%) specified the timeline in which GIS data were captured. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Of these 16 articles, 14 (88%) examined data collected within the past 10 years before publication 8,10-12,14,16-24 and 2 (13%) examined data from the past 11 to 20 years.…”
Section: Article Characteristicsmentioning
confidence: 99%
“…To date, studies have raised concern that community-level social risk may be an inaccurate proxy for individual social needs. 6,7 Consequently, the strength of their associations with clinical outcomes tends to be lesser than for the individual measures, a finding noted by Lipska and colleagues. 3 Furthermore, given that individuals living in areas with poor health care access may have high levels of unmet clinical need, and therefore suboptimal utilization patterns at baseline, there is concern that use of community-level variables in risk adjustment for payment determinations may reinforce underlying issues of structural racism and discrimination.…”
mentioning
confidence: 97%
“…The key disadvantage of area-level measures, however, is that they are prone to the very serious issue of ecological fallacy, whereby one makes erroneous assumptions about individuals based on aggregated data. To date, studies have raised concern that community-level social risk may be an inaccurate proxy for individual social needs . Consequently, the strength of their associations with clinical outcomes tends to be lesser than for the individual measures, a finding noted by Lipska and colleagues .…”
mentioning
confidence: 99%